Improvised McLAb apparatus for experiments in electricity and magnetism - Heriales, Abraham Moldes (Animo Repository, 1993)
An improvised multi-circuit laboratory (McLAB) apparatus was constructed using locally available materials. In addition, a laboratory manual designed to complement the McLAB apparatus was developed. Said laboratory manual covers ten experiments in electricity and magnetism. Both the laboratory manual and the McLAB apparatus were evaluated by 11 instructors and 22 students of the College of Engineering, University of Eastern Philippines. Results of the evaluation showed the following: 1) The improvised McLAB apparatus has an accuracy which is nearly identical with the commercial models. 2) The improvised McLAB apparatus could effectively substitute for the commercial models. 3) They are adaptable to the UEP classroom and/or laboratory conditions. 4) They are safe for student's use in performing the laboratory experiments. 5) The experiments could be performed by the students with the least help from the instructor. 6) The experiments help students to develop a positive attitude toward electricity and magnetism.